The most prominent problems of diabetes education in Iran: A qualitative content analysis - Faridokht Yazdani; Parvaneh Abazari; Fariba Haghani; Bijan Iraj (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Education in vulnerable communities can be a health affordable strategy to promote patient empowerment. Recognition and understanding the problems of diabetes education are of significance to overcome the barriers and advance the educational and care services to control diabetes and promotion of society health. The aim of this study was to explore participants' perspectives, experiences, and preferences, regarding diabetes education problems. MATERIALS AND METHODS: This descriptive, qualitative study was conducted from March 2016 to September 2017. The participants were 23 people including nine patients with diabetes and their family members and 14 members of diabetes healthcare team (physicians, nurses, and nutritionists). The data were collected through individual semi-structured interviews and analyzed through conventional content analysis approach proposed by Graneheim and Lundman. Some main categories and subcategories emerged. RESULTS: Three main categories showed the most prominent problems of diabetes education, namely, inadequate infrastructure for diabetes education, insufficient defined and de facto position for the role of diabetes nurse educator, and the failure in patient-oriented team approach in diabetes education. CONCLUSION: This article addresses the most important problems of diabetes education. The fundamental strategy to overcome these problems seems to be the planning and management of diabetes education as a high priority in the noncommunicable disease management policies of the Ministry of Health and Medical Education.